(untitled) (Tanzania Medical Journal, 2007)
Background: The School of Medicine at Muhimbili is the main doctor-training institution in the country. It runs a five-year MD programme taking 200 students annually. As for many schools in low-income countries, the majority of teachers have no formal training in educational theory Objective: To describe the physical and psychosocial learning environment from teachers' and students' perspectives, describe the perceptions of teachers and students of each other, and propose ways of improving the learning environment. Methods: Fourth year students of the 2005 graduating) class and selected clinical teachers took part in a survey to document their perceptions of the school's learning environment, and the perceptions of teachers and students of each other. Structured questionnaires designed by the authors were used for recording the required information from teachers and from students for analysis. Findings: The availability of ward patients suitable for clinical training was considered adequate by 84% of the students. However, less than 50% of students thought the wards, clinics, library and operating rooms provided a conducive learning environment. Only a third of the students said they used the Internet to access learning material. Two thirds of students said it was difficult to access teachers for consultation outside of scheduled classes. While 63% of students said teachers regularly showed them how to elicit physical signs on patients, a modest 58% of students perceived their teachers as professional role models. Only 13% of students felt that teachers avoided intimidating them during clinical teaching. Seventy one per cent of teachers provided feedback to students after clinical assessment, but only 21% of the teachers believed feedback to students should be directed towards identifying students' strengths and reinforcing them rather than seeking their weaknesses for correction. Conclusion: The learning environment at the school has some strengths that should to be amplified, and numerous weaknesses that need to be corrected in order to make the environment more conducive to teaching and learning. Tanzania Medical Journal Vol. 22 (1) 2007: pp. 9-11